Protecting the Gulf's marine ecosystems from pollution - Abu-Zinada, A. H. (Springer, 2017)
Biogeophysical setting of the Gulf / H.J. Barth and N.Y. Khan -- The coastal vegetation of the western and southern Gulf - characterisation and conservation aspects / G. Brown, B. Boer, S. Sakkir -- Impact of oil pollution and increased sea surface temperatures on marine ecosystems and biota in the Gulf / F. Krupp and A.H. Abuzinada -- Integrated management of pollution stress in the Gulf / N.Y. Khan -- Efforts of regional and international organisations in reducing levels of pollution in the Gulf / H.N. El-Habr and M. Hutchinson -- Oil pollution preparedness in the ROPME Sea Area / A.M.M. Al-Janahi -- Remote Sensing: A tool for managing marine pollution in the Gulf / R.A. Loughland and B. Saji -- Coastal Pollution in Bahrain and its management / K. Zainal, H. Al-Sayed and I. Al-Madnay -- Pollution from sea based sources / R. Facey -- Impacts of seawater desalination plants on the marine environment of the Gulf / S. Lattemann and T. Hopner -- Importance of the freshwater influx from the Shatt-Al-Arab River on the Arabian Gulf marine environment / F. Al-Yamani -- The compensation schedule approach frothe assessment of oil spill damages to marine resources of the RSA / S.M. Al-Ghais and W.H. Pearson -- The impact of the Gulf War (1990-91) oil release upon the intertidal Gulf coast line of Saudi Arabia and subsequent recovery / D.A. Jones, M. Hayes, F. Krupp, G. Sabatini, I. Watt and L. Weishar -- Rapid assessment indicators of oil spill recover in salt marsh ecosystems / H.J. Barth -- Shoreline bioremediation after the 1991 Gulf War oil spill / T. Hopner and K.A. Al-Shaikh -- Evaluation of arid salt marsh restoration techniques / L.Weishar, I. Watt, D.A. Jones and D. Aubrey.